Тhe classification of Easement - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Easement means, a right enjoyed by the owner of land over the lands of another: such as rights of way, right of light, rights of support, rights to a flow of air or water etc. The dominant tenement is the land owned by the possessor of the easement, and the servient tenement is the land over which the right is enjoyed. An easement must exist for the accommodation and better enjoyment to which it is annexed, otherwise it may amount to mere licence. An easement benefits and binds the land itself and therefore countinious despite any  change of ownership of either dominant or servient tenement, althought it will be extinguished if the two tenemants come into common ownership. An easement can only be enjoyed in respect of land. This means two parcels of land. First there must be a «dominant tenement» and  a «servient tenement». Dominant tenement to which the benefit of the easement attaches, and another (servient tenement) which bears the burden of the easement. A positive easement consist of a right to do something on the land of another; a negative easement restrict the use of owner of the serviant tenement may make of his land. An easement may be on land or on the house made on land. The next classification is on easement on the ground, and the other one under the ground. An easement shall be done in accordance with the principle of restrictions. This means that the less burden the servient tenement. When there is doubt about the extent of the actual easement shall take what easear the servient tenement. The new needs of the dominant estate does not result in the expansion of servitude. In the article is made comparison between The Draft Code  of property  and other real estate,  and The Draft of Civil Code of Serbia.